Inovasi teknologi pengolahan kerupuk Sagu fungsional berbasis Tepung Ikan Biang (Ilisha elongata) dimasa pandemi Covid-19 di Kube “Dian Lestari” Selat Panjang Kabupaten Kepulauan Meranti - Sumarto Sumarto; Desmelati Desmelati; Suparmi Suparmi; Dahlia Dahlia; Tjipto Leksono (Unri Conference Series: Community Engagement, 2021)
This activity aims to develop technological innovations for processing functional sago crackers with the fortification of the fish flour as a new variant of the business during the COVID-19 pandemic for Kube "Dian Lestari" Selatpanjang in the context of developing sustainable small industrial businesses in the Meranti Islands Regency, Riau Province. The method of implementing the activity is through counseling and direct training in the processing of sago crackers with the addition of 2% lead fish meal (20 g of fish flour from 1000 sago flour). The results of the service activities showed that all participants participated in the activities well, especially the Kube participants "Dian Lestari". The result of the product training activities was the making of sago functional (Biang fish). After deep-frying, they can get a new variant. The biscuits look neat and complete, and the color is bright gray. The taste of sago crackers becomes savorier, it tastes like fishing. The aroma of sago crackers is still dominant, typical of sago and a slight savory aroma of fish, with a crunchy and crumbly texture when eaten. The results of consumer assessments of functional sago crackers from giant fish have consumer acceptance in the "like and very like" category of up to 100%. The taste sensory factor determines the success of the new variant on the production of functional sago crackers with the fortification of 2% sago fish flour with a distinctive, savory, and delicious taste. The target of achieving 100% of the activities includes the participation of training participants, and the products produced. Characteristics of functional sago crackers (raw) have been nutrient content of 9.18% water, 3.75% protein, 1.48% fat, 0.66.6% ash, and 84.96% carbohydrates. Nutrient content of functional sago crackers of prickly fish (fried) has been moisture of 5.86%, protein 6.18%, fat 12.74%, ash 1.68%, and carbohydrates 73.54%.